Positive Darwinian selection is a driving force for the diversification of terpenoid biosynthesis in the genus Oryza - Chen, Hao (BioMed Central, 2014)
BACKGROUND: Terpenoids constitute the largest class of secondary metabolites made by plants and display vast chemical diversity among and within species. Terpene synthases (TPSs) are the pivotal enzymes for terpenoid biosynthesis that create the basic carbon skeletons of this class. Functional divergence of paralogous and orthologous TPS genes is a major mechanism for the diversification of terpenoid biosynthesis. However, little is known about the evolutionary forces that have shaped the evolution of plant TPS genes leading to terpenoid diversity. RESULTS: The orthologs of Oryza Terpene Synthase 1 (OryzaTPS1), a rice terpene synthase gene involved in indirect defense against insects in Oryza sativa, were cloned from six additional Oryza species. In vitro biochemical analysis showed that the enzymes encoded by these OryzaTPS1 genes functioned either as (E)-β-caryophyllene synthases (ECS), or (E)-β-caryophyllene & germacrene A synthases (EGS), or germacrene D & germacrene A synthases (DAS). Because the orthologs of OryzaTPS1 in maize and sorghum function as ECS, the ECS activity was inferred to be ancestral. Molecular evolutionary detected the signature of positive Darwinian selection in five codon substitutions in the evolution from ECS to DAS. Homology-based structure modeling and the biochemical analysis of laboratory-generated protein variants validated the contribution of the five positively selected sites to functional divergence of OryzaTPS1. The changes in the in vitro product spectra of OryzaTPS1 proteins also correlated closely to the changes in in vivo blends of volatile terpenes released from insect-damaged rice plants. CONCLUSIONS: In this study, we found that positive Darwinian selection is a driving force for the functional divergence of OryzaTPS1. This finding suggests that the diverged sesquiterpene blend produced by the Oryza species containing DAS may be adaptive, likely in the attraction of the natural enemies of insect herbivores. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-014-0239-x) contains supplementary material, which is available to authorized users.